2014
DOI: 10.3109/19396368.2014.955896
|View full text |Cite
|
Sign up to set email alerts
|

Functional features and protein network of human sperm-egg interaction

Abstract: Elucidation of the sperm-egg interaction at the molecular level is one of the unresolved problems in sexual reproduction, and understanding the molecular mechanism is crucial in solving problems in infertility and failed in vitro fertilization (IVF). Many molecular interactions in the form of protein-protein interactions (PPIs) mediate the sperm-egg membrane interaction. Due to the complexity of the problem such as difficulties in analyzing in vivo membrane PPIs, many efforts have failed to comprehensively elu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…The existence of the CD151 tetraspanin network in the equatorial segment of sperm and their interaction with the α6 subunit of presented α6β4/β1 integrin suggest a possibility of trans-interaction of both sperm and egg protein networks during sperm-egg membrane fusion. This is emphasized by the previously reported interaction between CD151 and CD9 tetraspanins in human oocyte with α3 integrin (CD49C) in spermatozoa 50 . Because the CD151 is most probably localized in the membrane environment, offering only the relatively small extracellular part to an interaction, the predicted N-terminal integrin domain contacts would correspond to an integrin interaction in its closed, www.nature.com/scientificreports www.nature.com/scientificreports/ folded state.…”
Section: Discussionmentioning
confidence: 84%
“…The existence of the CD151 tetraspanin network in the equatorial segment of sperm and their interaction with the α6 subunit of presented α6β4/β1 integrin suggest a possibility of trans-interaction of both sperm and egg protein networks during sperm-egg membrane fusion. This is emphasized by the previously reported interaction between CD151 and CD9 tetraspanins in human oocyte with α3 integrin (CD49C) in spermatozoa 50 . Because the CD151 is most probably localized in the membrane environment, offering only the relatively small extracellular part to an interaction, the predicted N-terminal integrin domain contacts would correspond to an integrin interaction in its closed, www.nature.com/scientificreports www.nature.com/scientificreports/ folded state.…”
Section: Discussionmentioning
confidence: 84%
“…Information found in PPIs databases supports the construction of interaction networks. All retrieved data from the various data sources (refer to [ 4 , 5 ]) were combined and loaded into Cytoscape 2.8 [ 13 ] to construct the protein interaction network (PIN). Two PINs for sperm proteins and oocyte proteins have been created, and then intersection (overlapping) network has been constructed using a network modification plugin (compare two networks) in Cytoscape.…”
Section: Methodsmentioning
confidence: 99%
“…Two PINs for sperm proteins and oocyte proteins have been created, and then intersection (overlapping) network has been constructed using a network modification plugin (compare two networks) in Cytoscape. Because our primary aim was to identify protein candidates involved in sperm-egg interactions, we extracted only the proteins that contain a signal sequence and/or transmembrane domain [ 14 ] by selecting signal peptide and transmembrane features from sequence annotation (features) in an extensively curated UniProt database ( www.uniprot.org ) (for more details refer to [ 4 , 5 ]).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rubinstein et al (1996) found out that CD9 as well as CD63, CD81 and CD82 organize a complex with other associated molecules as the VLA integrins and HLA-DR antigens. Recently, interactions between CD9 and CD49B, CD63 and IZUMO1 during human fertilization were predicted using several computational approaches (Sabetian et al 2014). Some authors (Ellerman et al 2003) concluded CD9 as a receptor for PSG17 (a member of pregnancy-specific glycoprotein family), which, similar to IZUMO, is a member of the immunoglobulin superfamily.…”
Section: What Is the Role Of Cd9 In Reproduction?mentioning
confidence: 99%